Voltage Profile Improvement with Combined UPFC and IPFC Facts Devices: A Review - Kaswii, Violet; Saulo, Michael Juma (Multidisciplinary Journal of Technical University of Mombasa, 2020)
The interline power flow controller (IPFC) and the unified power flow controller (UPFC) are both advanced types of flexible AC transmission systems (FACTS). These devices can provide the power system with control of voltage, and that of real and reactive power. This paper reviews the literature on UPFC and IPFC FACTS devices in voltage control and covers two main areas of research (i) voltage control using FACTS devices, and (ii) UPFCs / IPFCs and their applications in power systems. FACTs devices are applied in modern power system networks for the purpose of voltage control while at the same time providing enhanced power system stability. Research has shown that their benefits in the long run outweighs their high cost especially when they are optimally sized and located in the power network. Moreover, in the planning of power transmission systems, a Multi-Criteria Decision Making (MCDM) technique can help in the incorporation of both the costs and technical viability. This approach provides techno-economic optimization and at the same time meeting environmental criteria.